Nothing ventured, nothing gained - Hermann Hauser (EIB Papers, 2001)
Even though the industrial revolution started in Europe, many commentators suggest that European entrepreneurship has become an oxymoron. The facts of the case are, however, growing against them. For instance, Europeans nowadays run a fair share of Silicon Valley companies. Examples include phone.com - one of the most successful new mobile software companies - or LSR logic, a major semi-conductor business. At the same time Europeans have established enterprises that have become respected leaders in mobile telephony as well as in the data communication sector - well known examples here include Ericsson, Nokia and Vodafone. The 'old' continent clearly is swiftly re-discovering its entrepreneurial genes in creating a number of successful companies worldwide. It is, however, venturing in a different direction. While the era of the PC belongs to the US, Europeans are betting far more heavily a future era of wireless communications.
Keywords: 330; Risikokapital; Entrepreneurship-Ansatz; Wirtschaftswachstum; Vergleich; EU-Staaten; USA